SIFAT VENIR DAN KAYU LAPIS BEBERAPA JENIS KAYU INDONESIA - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1986)
This report  deals with peeling,  physical  and  mechanical properties  of  veneer and some physicai   and  mechanical properties  of  plywood (triply)  of  16 wood species from  East  Kalimantan  and  1 species from   West  Java.  The logs  of  all wood species tested could  be peeled  without heating or steaming.   Veneer of 0.9 mm  and 1.5 mm  in thickness  could be peeled  at cutting  angles between  89° and 92°.The yield  of green veneer was 46. 7%  and the average shrinkage  was 10. 7%  with a minimum   of  5.9% (jabon) and  maximum   of  13.9%  (merembung).   Thickness  swelling from  oven dry to air dry varied between 2. 7%  (medang tanduk)  and 3.9%(nyatoh)  with an average of 3.4%.The bonding strength  of plywood  made  of 5 wood species (29. 4%) was in complience  with the Indonesian  standard for  type  II  or water resistant,  11 wood species (64. 7%) with  Japanese  standard  and  6 species (35.3%) with German standard.The average thickness reduction  due to pressing  pressure  was 0.23 mm  with minimum  of 0. 07 mm (buah sayap)  and  maximum  of 0.44 mm (merant imerah).The specific gravity  of  wood used in this experiment  varied between 0.30  (merembung)  and 0. 80 (kapur).  The specific gravity  of plywood ranged from   0.46 (jabon) to 0.89 (medang tanduk).The  average values of  bending  strength  parallel  and perpendicular  to grain of  3 mm  triply  were 1221.29 kg/cm2   and  603.68 kg/cm2, respectively.  The tensile strength parallel and perpendicular  to grain were 625.95 kg/cm2  and 539.93 kg/cm2,  respectively.  The average values for bending strength parallel and perpendicular  to grain of 4 mm triply were  1096.31 kg/cm2  and 398.8 kg/cm2,   respectively.  The tensile  strengths parallel and perpendicular  to grain were 696.46 kg!/cm2  and 443.95 kg/cm2, and 443.95 kg/cm2.   respectively.